Alerting System for Sport Activity Based on ECG Signals using Proportional Integral Derivative - Vika Octaviani; Arief Kurniawan; Yoyon Kusnendar Suprapto; Ahmad Zaini (IAES Indonesia Section, 2017)
Exercise makes the body fit, but most people do not know the intensity of the exercise they are doing right or otherwise can be dangerous, because not everyone knows the maximum heart rate (MHR), Heart Rate Resting (HRRest), heart rate reserve (HRR) and Target Heart Rate (THR) for each individual, it is proposed an ECG signal-based warning system to find out how much a person's maximum limit in exercise based on age, gender, body mass index, MHR, RHR, THRmin and THRmax. The data is taken by using ECG sensors from the subjects who are doing sport activities using a treadmill by noting the resulted feature when the subject reaches the maximum limit of the heart rate (THRmax) target. Range is calculated from 50% of the THR value, which increases periodically during treadmill activities up to 85% of THR. When already exceed THRmax, then the system will automatically warn and decrease the level of exercise to medium to low levels in the cooling down level. For the % hardware errors in a row from 1 minute, 3 minutes, 5 minutes, and 10 minutes obtained % error with 0.77±0.14. The RMSE of the hardware and software test showed high accuracy because of the small value of error. The system succeeds to alert any intensity level of sport based on the Proportional integral derivative according to the bpm value generated by the subject during the treadmill exercise.